+0  
 
0
5138
2
avatar+8 

A sequence is defined recursively by the formula f(n + 1) = f(n) + 3 . The first term of the sequence is –4. What is the next term in the sequence?

EyasiaJ  Jun 17, 2015

Best Answer 

 #2
avatar+27061 
+10

Or just:

 

f(1) = -4

 

f(2) = f(1) + 3   so f(2) = -4 + 3  or f(2) = -1

Alan  Jun 17, 2015
 #1
avatar
+10

using notation is just a fancy way of describing a sequence.

is the number you're currently at, so with that logic n+1 is the term after it in the sequence.

f(n) is the function using n as the input.

so you know that the first term of the sequence is -4, or f(n)= -4.

In order to find f(n+1) plug in what you know for f(n).   $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = {f}{\left({\mathtt{n}}\right)}{\mathtt{\,\small\textbf+\,}}{\mathtt{3}}$$ we know that f(n) = -4, so it is substituted in to the equation given. $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = {\mathtt{\,-\,}}{\mathtt{4}}{\mathtt{\,\small\textbf+\,}}{\mathtt{3}}$$ now simplify! $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = -{\mathtt{1}}$$   hope this helps!
Guest Jun 17, 2015
 #2
avatar+27061 
+10
Best Answer

Or just:

 

f(1) = -4

 

f(2) = f(1) + 3   so f(2) = -4 + 3  or f(2) = -1

Alan  Jun 17, 2015

32 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.